Teaching literature to adolescents - Beach, Richard (Erlbaum, 2006)
"This text for preservice and inservice English education courses presents current methods of teaching literature to middle and high school students. The methods are based on social-constructivist/socio-cultural theories of literacy learning, and incorporate research on literary response conducted by the authors."--BOOK JACKET.